2012
DOI: 10.1002/prep.201100020
|View full text |Cite
|
Sign up to set email alerts
|

Explosive Strength and Impact Sensitivity of Several PBXs Based on Attractive Cyclic Nitramines

Abstract: Plastic explosives based on different cyclic nitramines with different polymeric matrices were prepared and studied. The used polymeric matrices were fabricated on the basis of polyisobutylene (PIB), acrylonitrile‐butadiene rubber (ABR), Viton A, and polydimethyl‐siloxane as binders, whereas the nitramines named RDX (1,3,5‐trinitroperhydro‐1,3,5‐triazine), β‐HMX (β‐1,3,5,7‐tetranitro‐1,3,5,7‐tetrazocine), BCHMX (cis‐1,3,4,6‐tetranitrooctahydroimidazo‐[4,5‐d]imidazole) and ε‐HNIW (ε‐2,4,6,8,10,12‐hexanitro‐2,4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 14 publications
2
30
0
Order By: Relevance
“…The charge casings were steel with an average wall thickness of 4.5 mm. Regarding the literature, several types of plastic explosives can be used for filling the charge cases, such as the French plastic explosive named Formex P1 [17] and the American plastic explosive Composition C4 [18][19]. Selection of the plastic explosive was based on performance and sensitivity to different stimuli [20][21][22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The charge casings were steel with an average wall thickness of 4.5 mm. Regarding the literature, several types of plastic explosives can be used for filling the charge cases, such as the French plastic explosive named Formex P1 [17] and the American plastic explosive Composition C4 [18][19]. Selection of the plastic explosive was based on performance and sensitivity to different stimuli [20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…point to the target surface as explained in Section 1. Table 4 presents the penetration depth calculated using various methods, including the modified virtual origin model (Equation 19) from Section 2, the classic V.O. model, the numerical simulation and the experimental depth of penetration, as well as the penetration reduction due to the density gradient (deficit/reduction).…”
Section: The Penetration Depth Calculationsmentioning
confidence: 99%
“…Previous research has shown that reducing the size of solid filler particles can solve these problems and also enhance the burning rate of propellants [11][12][13][14]. In addition, the mechanical sensitivity of CMDBs can be decreased if the particles coated with some binders [15][16][17][18]. Nitrocellulose (NC) is necessary for the energy and mechanical properties of double-base propellants.…”
Section: Introductionmentioning
confidence: 99%
“…BCHMX had been studied as an energetic filler bonded by C-4 matrix 5,6 . Plastic bonded explosives based on BCHMX and fluorinated binders have been studied [7][8][9] . Also replacement of PETN by BCHMX in SEMTEX10 has been investigated 10 .…”
Section: Introductionmentioning
confidence: 99%